English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Compare the graph of h(x) to the graph of f(x). Explain the transformation in words h(x = f (x+2) -3.

2006-11-25 14:58:56 · 3 answers · asked by rlvitte 1 in Science & Mathematics Mathematics

3 answers

If h(x) = f(x+2) - 3, then h(x) is the same as f(x) shifted 2 to the left and 3 down.

2006-11-25 15:04:28 · answer #1 · answered by Jim Burnell 6 · 0 0

y=f(x)+c, shift the graph of y=f(x) a distance c units upwards
y=f(x) - c, shift the graph of y=f(x) a distance c units downwards
y=f(x-c), shift the graph of y=f(x) a distance c units to the right
y=f(x+c), shift the graph of y=f(x) a distance c units to the left
y=cf(x), stretch the graph of y=f(x) vertically by a factor of c
y=(1/c)f(x), compress the graph of y=f(x) vertically by a factor of c
y=f(cx), compress the graph of y=f(x) horizontally by a factor of c
y=f(x/c), stretch the graph of y=f(x) horizontally by a factor of c
y= --f(x), reflect the graph of y = f(x) about the x-axis
y=f(-x), reflect the graph of y=f(X) about the y-axis

when you have an inverse function the graph of the inverse is a reflection in the y=x line of the original function.

and finally when adding two function f(x+z) you can just add the values of y at each similar value of x and get the new (x,y) co-ordinate.

2006-11-25 23:55:07 · answer #2 · answered by xian gaon 2 · 0 0

h is f shifted by 2 units to the left and 3 units down.

2006-11-25 23:02:05 · answer #3 · answered by Anonymous · 1 0

fedest.com, questions and answers